THE RELATIONSHIP BETWEEN SELF CONTROL AND STUDENTS' TRUNITY BEHAVIOR AT SMAN 10 MERANGIN - Hadi, Fuji (Jurnal Kopendik, 2025)
Truancy is a form of disciplinary violation that negatively affects the learning process and students’ character development. This phenomenon has become a concern at SMAN 10 Merangin, prompting this study to examine the relationship between self-control and students’ truancy behavior. The research employed a quantitative approach with a correlational design. The population consisted of 49 grade XI students selected through a total sampling technique. Data were collected using a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis included normality, linearity, and Pearson Product Moment correlation tests. The findings revealed that truancy behavior was in the high category (69%), while students’ self-control was also high (73.55%). The correlation coefficient of -0.616 with a significance value of 0.000 indicated a negative and significant relationship between self-control and truancy. This means that the higher the students’ self-control, the lower their tendency to skip classes.